Bridging the Tactile Gap: Evaluating Virtual Reality (VR) Laboratories in Distance Life-Science Curricula - Ruth Rize Paas Megahati S; H. L. M. Mohideen (RADINKA JAYA UTAMA PUBLISHER, PADANG< INDONESIA, 2026)
The persistent expanding trajectory of distance education within higher biological sciences has encountered structural friction regarding the